G Protein-coupled Receptor (GPCR) Signaling via Heterotrimeric G Proteins from Endosomes - Tsvetanova, Nikoleta G. (J Biol Chem, 2015)
Some G protein-coupled receptors (GPCRs), in addition to activating heterotrimeric G proteins in the plasma membrane, appear to elicit a “second wave” of G protein activation after ligand-induced internalization. We briefly summarize evidence supporting this view and then discuss what is presently known about the functional significance of GPCR-G protein activation in endosomes. Endosomal activation can shape the cellular response temporally by prolonging its overall duration, and may shape the response spatially by moving the location of intracellular second messenger production relative to effectors.